The Impact of Financial Literacy, Overconfidence Bias, Herding Bias and Loss Aversion Bias on Investment Decision - Rafandito Mahendra Nugraha Prayudi; Eko Purwanto (PT FORMOSA CENDEKIA GLOBAL, 2023)
Investment decisions, aimed at securing long-term gains, are shaped by rational and irrational attitudes in capital allocation. Financial literacy gauges the rational stance, while behavioral finance dissects irrational inclinations. Behvioral finance includes overcondience bias, herding bia and loss aversion bias. This study scrutinizes how financial literacy, overconfidence bias, herding bias, and loss aversion bias sway investment choices for young Java Island investors. Simple random sampling is used, analyzed via Partial Least Square. Results indicate financial literacy lacks significant impact. Overconfidence boosts decisions, while high herding bias hampers them. Loss aversion bias, however, holds no sway on Java Island investors' decisions.